PENGARUH STRUKTUR KEPEMILlKAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI INTERVENING - Sugiarto, Melanie (Widya Mandala Surabaya Catholic University, 2011)
Increasing the firm value is one of the main purposes of a company. Increasing the firm value means the slOck return gives the optimal return to the investors. The main objective of the present study is to expand researches in analyzing the impact of managerial ownership, institutional ownership, and dividend policy to the firm value, either directly or indirectly with debt policy as the intervening variable. Population in this study are public companies listed in Indonesia Stock Exchange that are not included in the categories of banking industry, institution of credit matters, security, and insurance, for an observation period of 2003 to 2007. Data were collected through purposive sampling and 64 firms were taken as sample. The analysis method used in this study is multiple linear regressions expanded with path analysis using the SPSS 16.0. The results of this study show that: (1) managerial ownership had direct negative impact to firm value and didn if have indirect impact to firm value with debt policy as the intervening variable; (2) institutional ownership had no direct and indirect impact to firm value; and (3) dividend policy had direct negative impact to firm value and indirect positive impact to firm value with debt policy as the intervening variable.